Examining the Impact of Interdisciplinary Collaboration among Health Administration, Community Health, Sociology, and Rehabilitation Specialists on Healthcare Quality and Patient Outcomes: A Qualitative Study - Ali Hussain Abdulmohsen Albeladi,; Sami Habeeb Ali Almubarak,; Sana Mansour Yousef Hameed,; Murtadha Abdullah Abbas Alsaeed,; Abdulrhman Abdulaziz Sulaiman Al Homidan, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Interdisciplinary collaboration in healthcare has gained increasing attention as a means to improve the quality of care and patient outcomes. This qualitative study aims to examine the impact of collaboration among health administration, community health, sociology, and rehabilitation specialists on healthcare quality and patient outcomes. Semi-structured interviews were conducted with 20 healthcare professionals from various disciplines in a large urban hospital. Thematic analysis revealed five main themes: (1) enhanced communication and information sharing, (2) improved care coordination and continuity, (3) increased patient satisfaction and engagement, (4) better management of complex cases, and (5) challenges in implementing interdisciplinary collaboration. The findings suggest that interdisciplinary collaboration can lead to more comprehensive and patient-centered care, but requires supportive organizational structures, clear role definitions, and ongoing training and facilitation. This study highlights the potential benefits and challenges of interdisciplinary collaboration and provides insights for healthcare organizations seeking to improve care quality and patient outcomes.